Displacement-stress Distribution in a Femoral Bone by Optical Methods. (2015) - Takacs, Ioana Alexandra; Botean, Adrian Ioan; Hardau, Mihail; Chindris, Stefan
Abstract: The use of optical methods to study the field of displacements and state of stresses of the femoral bone involves identifying their applicability limits. The aim of this study is to apply these two methods for the analysis of the field of displacements and state of stresses of an isotropic compressed 3D model of a human femoral bone and highlighting the advantages and disadvantages of these two optical methods. It was shown that if the cast model respects only the outer geometry (isotropic model) of the femoral bone the area where the maximum stresses occurs is the diaphyseal area instead of the femoral neck area, as shown in literature.